2019
DOI: 10.4103/ija.ija_267_19
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction of papers authored by Yuhji Saitoh – Beyond the Fujii phenomenon

Abstract: Background and Aims: Various aspects of retracted articles authored by Yoshitaka Fujii and their retraction notices have been examined. Yuhji Saitoh has coauthored many articles with Yoshitaka Fujii which were subsequently retracted. Japanese Society of Anesthesiology (JSA) recommends retraction of various articles by Yuhji Saitoh, but various attributes of those and their retraction notices have not been examined. Methods: A list of retracted articles was retrieved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Wray and Andersen ( 2018 ) found that more than 50% of retractions were due to errors in the journal Science . Saikia and Thakuria ( 2019 ) examined the various aspects of retracted articles authored by Yoshitaka Fujii. McHugh and Yentis ( 2019 ) analyzed how long been taken for retraction of papers authored by Scott Reuben, Joachim Boldt and Yoshitaka Fujii.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Wray and Andersen ( 2018 ) found that more than 50% of retractions were due to errors in the journal Science . Saikia and Thakuria ( 2019 ) examined the various aspects of retracted articles authored by Yoshitaka Fujii. McHugh and Yentis ( 2019 ) analyzed how long been taken for retraction of papers authored by Scott Reuben, Joachim Boldt and Yoshitaka Fujii.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Examining the retractions has been of growing interest in recent times. Aspura et al ( 2018 ), Bhatt ( 2021 ), Campos-Varela et al ( 2020 ), Elango et al ( 2019 ), Moradi et al ( 2018 ), Rubbo et al ( 2019 ), Samuel et al ( 2020 ), Saikia and Thakuria ( 2019 ), and Wray and Andersen ( 2018 ) are examples of such investigations. These studies are focused on a single country or discipline or journal or author.…”
Section: Introductionmentioning
confidence: 99%
“…In this highly competitive world of "publish or perish," we happen to violate research and publication ethics quite a number of times knowingly or unknowingly. Hence, in the race for promotion, let us not do something that can lead to the retraction of the publication and a lifetime of regrets [3][4][5][6] . For a scientific journal, it is essential to follow the ethical principles in scientific publications to maintain the readers' trust and to uphold its reputation 7 .…”
mentioning
confidence: 99%
“…Research misconduct can take place at any stage of research continuum, from proposal writing to publication 8 . The Committee on Publication Ethics (COPE), World Medical Association (WMA), World Association of Medical Editors (WAME), International Committee of Medical Journal Editors (ICMJE), Good Clinical Practice (GCP), Retraction Watch, and the Office of Research Integrity (ORI) are few of the prominent organisations that have taken many initiatives, and formed guidelines to maintain the highest ethical conduct in research and publication 3,[8][9][10][11] . The simplest way to avoid violating the ethical principles is to understand what they constitute and mean.…”
mentioning
confidence: 99%